Genetic diversity and offspring fitness in the red and white fruit color morphs of the wild strawberry Fragaria pentaphylla. (7th December 2019) - Chen, Lu-Xi; Xu, Su-Ting; Ding, Wei-Hang; Li, Jun-Min; Alpert, Peter
Abstract: Aims: Fruit color polymorphisms are widespread in plants, but what maintains them is largely unclear. One hypothesis is that some morphs are preferred by dispersers while others have higher pre- or postdispersal fitness. This leads to the prediction that fruit color morphs will differ in pre- or postdispersal fitness. Methods: We compared genetic and clonal diversity, mating system, morphological traits that might be associated with resistance to freezing, and germination, survival and seed production of progeny of the red and white fruit morphs in a population of a diploid, wild strawberry, Fragaria pentaphylla, from south-central China. Important Findings: The red morph was much more abundant than the white but did not show higher genetic diversity as measured by observed and effective numbers of alleles, Shannon information index, or expected or observed heterozygosities. AMOVA showed that most of the genetic variation in the population was within rather than between morphs. Morphs did not differ in mating system parameters, and no significant biparental inbreeding was found in either morph. Gene flow between two morphs was high ( N m = 6.89). Seeds of the red morph germinated about 2 days earlier and had a 40% higher rate of germination than those of the white morph, but survival of seedlings and seed production by surviving offspring did not differ between morphs. The whole postdispersal fitness of the red morph was about two times higher than that of the white morph. Red morphs had hairier petioles but not more surface wax on leaves. Overall, results showed partial evidence for difference in pre- and postdispersal fitness between fruit color morphs in F. pentaphylla . Differences in fitness independent of dispersal may thus partially account for fruit color polymorphism in all cases.